Hierarchical Role-Based Access Control for Multi-User Collaborative CAD Environment. Issue 3 (3rd May 2016) - Teng, Chia-Chi; Mensah, Francis N.; Ekstrom, J.; Helps, Richard; Jensen, C. Greg
ABSTRACT: Commercial computer aided design (CAD) applications have traditionally been based on a single user architecture. Recent research on multi-user collaborative CAD and other computer aided applications (CAx) have shown promising and highly functional prototypes of multi-user concurrent designing tools based on popular and market leading commercial software systems such as Siemens NX. However, for these prototypes to be deployed to the real-world corporate environment for commercial projects, security features such as access control and encrypted transport must be implemented as integral part of the enterprise network infrastructure. Directory services (DS) such as Microsoft Active Directory and Lightweight Directory Access Protocol (LDAP) has become the standard software and protocol for managing resources in the complex modern enterprise network. DS controller authenticates and authorizes user's access to resources and enforces security policies. This research presents a method to integrate existing corporate DS and user information to provide a role-based access control functionality in multi-user CAD software. A successful prototype system was built based on previously published multi-user enabled Siemens NX CAD software and integrated with a Microsoft Active Directory domain services where users and roles where created to simulate a corporate engineering organization. The system was then validated with models and assemblies where components were configured with various access privileges. GRAPHICAL ABSTRACT: